Study of effect of loading rate on fracture toughness of SA516Gr.70 steel for nuclear pressure vessel and piping in DBTT regime and evaluation of shift in reference transition temperature. (December 2020) - Sharma, S.; Samal, M.K.
Graphical abstract: Highlights: Effect of impact velocity on cleavage fracture toughness of SA516Gr.70 steel is studied. Two different loading rates, viz., 0.5 and 700 m/min are used in fracture experiments. Scatter in fracture toughness increases with loading rate due to elevated stress fields. Scatter in fracture toughness is found to be bounded well by 5% and 95% master curves. Value of T0 changes from −100 to −10 °C when loading rate changes from 0.5 to 700 m/min. Abstract: The objective of this work is to quantify the effect of loading rate on scatter as well as temperature-dependence of cleavage fracture toughness data of SA516 Gr.70 steel in the ductile-to-brittle transition temperature (DBTT) regime. This steel is a relatively high strength grade carbon steel and it is used for fabrication of nuclear pressure vessels, transportation casks and pipings etc. For integrity analysis in radioactive environment, the concept of master curve according to ASTM E1921 is used and the reference temperature T0 is evaluated from experimental data. The purpose of this work is to evaluate the change in T0 due to increase in loading rate when fracture specimens are tested in a modified split Hopkinson pressure bar (SHPB) test setup. In this work, a specially designed SHPB type test setup has been used to carry out the fracture tests using sub-sized single-edged notched bend specimens at a loading rate 700 m/min. The data from SHPB tests have been compared with those obtained from a lower loading rate of 0.5 m/min. From the results of the tests, it was observed that the median value as well as the scatter in fracture toughness increases with temperature in the DBTT regime for both the loading rates. For higher loading rate, the median values of fracture toughness increases slowly with temperature. The value of T0 was found to increase from −100 °C at 0.5 m/min to −10 °C at 700 m/min loading rate, signifying a positive shift in reference temperature with increase in loading rate. The reason for the observations regarding the variation of experimental data with loading rate has been explained from the point of view of micro-mechanism of the fracture process.